A COMPARATIVE ANALYSIS OF INTERNATIONAL AND MONGOLIAN APPROACHES TO QUANTIFYING AND ADDRESSING PSYCHOLOGICAL DAMAGES - Otgonsuren Chuluun (International Journal of Innovative Technologies in Social Science, 2025)
In our country, Article 16, Paragraph 14 of the Constitution of Mongolia states that if a person considers their rights and freedoms guaranteed by Mongolian law and international treaties to have been violated, they have the right to appeal to the court and seek compensation for damages illegally caused by others. This provision establishes the legal foundation for filing complaints and seeking remedies for psychological harm caused by criminal acts. However, despite legal reforms improving regulations on compensation for tangible damages to a person's body and property in the Civil Code, Civil Procedure Code, Criminal Code, Criminal Procedure Code, and Forensic Examination Law, the legal framework for remedying and determining compensation amounts for non-material damages, particularly psychological harm, remained undefined until recently.The Civil Code, Civil Procedure Code, Criminal Code, and Criminal Procedure Code lack provisions defining psychological harm, specifying which crimes warrant compensation for such harm, what requirements should be met for calculation, and what criteria should be applied.Due to this inadequate legal regulation, victims of crimes are unable to fully exercise their rights to receive complete and fair compensation for their damages.On one hand, when calculating damages for loss of life, health, emotional distress, or psychological harm caused by criminal acts in Mongolia, courts have only been considering evidence-based costs such as medical treatment, funeral expenses, and transportation costs. In other words, courts have only been calculating actual material damages, while non-material damages such as emotional distress or psychological harm have remained undefined and consequently uncompensated.On the other hand, victims of crimes who have suffered emotional distress or psychological harm have not been claiming compensation for their psychological damages, and the few claims filed in court have been dismissed, failing to provide genuine protection of human rights. However, the current situation has improved with the final approval of the revised Forensic Examination Law, which regulates the forensic examination process in detail and incorporates provisions for determining the severity of psychological harm (commonly referred to as emotional distress) through forensic examination, allowing courts to assess monetary compensation and settle damages. Amendments have been made to criminal and civil legislation accordingly.